Possibilities and Opportunities for Undertaking the Liturgical Education of Children in The Archdiocese of Samarinda, East Kalimantan, Indonesia - Silpanus Silpanus (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2021)
This article discusses possibilities and opportunities for undertaking the liturgical education of children. Liturgical education is very important for every person in the Church-from bishops, priests, and seminarians, to lay people. But a suitable and proper liturgical education should begin gradually from an early age, from childhood to adulthood. Liturgical education should begin from childhood so that growing up into mature and responsible adult children can truly be strong pillars for the future of the Church and of society. Liturgical education of children in the Archdiocese of Samarinda faces the various challenges and the possibilities obtaining in the Archdiocese. The Archdiocese of Samarinda has programs that concern the liturgical education of children. This liturgical education of children programs is expected to be able to help faces various challenges in the Archdiocese and find a new solution that make the programs more effective and stimulating.